A novel genome sequence of Jasminum sambac helps uncover the molecular mechanism underlying the accumulation of jasmonates. (26th November 2022) - Xu, Min; Gao, Qiang; Jiang, Mengwei; Wang, Wenling; Hu, Juan; Chang, Xiaojun; Liu, Dinggao; Liang, Yuwei; Jiang, Yifan; Chen, Fei; Li, Chuhao; Huang, Haoran; et al.
Abstract: Jasminum sambac is a well-known plant for its attractive and exceptional fragrance, the flowers of which are used to produce scented tea. Jasmonate (JA), an important plant hormone was first identified in Jasminum species. Jasmine plants contain abundant JA naturally, of which the molecular mechanisms of synthesis and accumulation are not clearly understood. Here, we report a telomere-to-telomere consensus assembly of a double-petal J. sambac genome along with two haplotype-resolved genomes. We found that gain-and-loss, positive selection, and allelic specific expression of aromatic volatile-related genes contributed to the stronger flower fragrance in double-petal J. sambac compared with single- and multi-petal jasmines. Through comprehensive comparative genomic, transcriptomic, and metabolomic analyses of double-petal J. sambac, we revealed the genetic basis of the production of aromatic volatiles and salicylic acid (SA), and the accumulation of JA under non-stress conditions. We identified several key genes associated with JA biosynthesis, and their non-stress related activities lead to extraordinarily high concentrations of JA in tissues. High JA synthesis coupled with low degradation in J. sambac results in accumulation of high JA under typical environmental conditions, similar to the accumulation mechanism of SA. This study offers important insights into the biology of J. sambac, and provides valuable genomic resources for further utilization of natural products. Abstract : High jasmonate (JA) synthesis coupled with low degradation in Jasminum sambac results in high accumulation of JA under typical environmental conditions